IS ACUTE APPENDICITIS ASSOCIATED WITH INACTIVE ULCERATIVE COLITIS A PARTICULAR CASE OF DISSOCIATION OF THE MECHANISMS OF IMMUNE DEFENCE WITHIN THE APPENDIX AND THE COLON? IMPLICATIONS IN CLINICAL PRACTICE - Velciov, Silvia; Gluhovschi, Cristina; Petrica, Ligia; Duta, Ciprian; Cornianu, Marioara; Gluhovschi, Adrian; Timar, Romulus; Gluhovschi, Gheorghe (European Scientific Journal, ESJ, 2014)
Introduction: The presence of a well-known immune system within the bowel and the appendix, a genuine lymphoid organ, imposes a thorough analysis of the inter-relation between those two segments of the digestive tract (in the course of acute appendicitis associated to inactive ulcerative colitis), from an anatomical and functional perspective. Design. We present a case of acute gangrenous appendicitis in an 80 yearold female patient with ulcerative colitis (UC) and history of repeated episodes of disease, diagnosed 18 years prior to acute appendicitis. Acute appendicitis occurred with no signs of active UC. Results. The case presented with diagnostic difficulties which led to delayed surgery. This was related to the age of the patient (80 years), in which acute appendicitis is very rare. Also, the clinical picture of acute gangrenous appendicitis associated to inactive ulcerative colitis is unusual in clinical practice. After surgery, the patient developed a suppurated process which required drainage for one month. Despite favouring conditions, activity of UC (an expected phenomenon) was not observed. Conclusions: This particular situation of an inactive UC associated to acute appendicitis and protracted suppurated process after surgery raised the disscution of the dissociation of the appendicular immune system from that one of the colon in the course of ulcerative colitis (UC). This case pleads for a strong inter-relation between immunology and clinical practice, both of which are complementary.